1960
DOI: 10.1111/j.1365-2672.1960.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Intestinal Flora of the Pig. Iv. The Effect of Dietary Supplements of Penicillin, Chlortetracycline or Copper Sulphate on the Faecal Flora

Abstract: SUMMARY Streptococci, lactobacilli and coli‐aerogenes organisms were isolated from pigs receiving penicillin, chlortetracycline or copper sulphate as dietary supplements. Changes in their numbers, physiological type and sensitivity to the supplements fed are described. Penicillin and chlortetracycline rapidly induced a population resistant to the antibiotic fed, but no changes were detected in numbers or types of organisms isolated. Copper sulphate caused a reduction in the numbers of streptococci and a change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
3

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 18 publications
5
44
0
3
Order By: Relevance
“…This agrees with our previous findings (Fuller et al 1960) that S. equinus strains isolated from pig faeces were difficult to group unless concentrated extracts were used. It may also explain past failures to detect a group specific antigen.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This agrees with our previous findings (Fuller et al 1960) that S. equinus strains isolated from pig faeces were difficult to group unless concentrated extracts were used. It may also explain past failures to detect a group specific antigen.…”
Section: Discussionsupporting
confidence: 83%
“…It is now well established that the streptococci are one of the predominant groups of organisms in the intestine of the pig (Raibaud & Caulet, 1957;Fuller et al 1960). Consequently the classification of streptococci from this source has recently attracted much attention and many different species have been described as predominating in the pig gut.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surprisingly few studies have been conducted to investigate the effect of high levels of Cu on the microbiota in the gastrointestinal tract of pigs. Fuller (1960) found that in pigs fed copper sulphate the numbers of lactobacilli and coliform organisms remained unaffected, but there was a marked fall in the number of streptococci. The extent of the reduction varied but the counts of streptococci in the treated pigs were always lower than in the control pigs and the reduction could be as much as from 10 9 to 10 3 counts per g faeces.…”
Section: Coppermentioning
confidence: 93%
“…In fact poultry coliforms (Enterobacteriaceae, Proteobacteria) are more susceptible to copper than gram positives as Lactobacillus (Firmicutes) [9] . Early studies suggested a relative tolerance of lactobacilli and Escherichia coli to copper as dietary supplement [10] . The possible effects of copper on the normal microbiome were not listed among the biological effects of copper human exposure [4] .…”
Section: Introductionmentioning
confidence: 99%